Redefinisi Pendidikan Seni: Analisis Psikopedagogis dan Revitalisasi Kearifan Lokal Minangkabau Di Universitas Negeri Padang - Ega Harna B; Neviyarni S; Herman Nirwana (JURNAL ARMADA PENDIDIKAN, 2026)
Fine arts education in higher education is often trapped in a dichotomy between industrial demands and bureaucratic formalism, which potentially triggers an "erosion of meaning" and "psychological exhaustion" within the academic community. This research aims to identify critical gaps between art education practices in the Fine Arts Education Study Program at Universitas Negeri Padang (UNP) and the fundamental psychological needs of students and lecturers. Using a Critical Educational Criticism approach, this study analyzes the institutional ecology, including human resources, infrastructure, and curriculum structure. The findings indicate a systemic neglect of fundamental psychological principles, particularly Self-Determination Theory (autonomy, competence, and relatedness), Subjective Well-being, and the failure to integrate humanistic psychology into the art criticism process. Furthermore, a dissonance was identified between Western educational models and the Minangkabau cultural matrix, leading to identity alienation among students. As a strategic solution, this research proposes the paradigm of "Pendidikan Seni Terapeutik Berbasis Kearifan Lokal" through the revitalization of the "Neo-Surau" model and the "Mamak Akademik" mentorship system. The implementation of the egalitarian "Lingkaran Randai" art criticism format is proposed to create a safe space that humanizes and heals. In conclusion, the integration of modern psychology with local ethnopedagogical values is key to transforming art education into an empowering and sustainable process.